Learn key skills in software engineering craftmanship course. (Pragmatic AI Solutions, 2022)
Learn Key Skills in Software Engineering Craftmanship Course An Ongoing Course This video will show you how to use CUDA GPUs with Python. Lessons Covered Include: Introduction to course What is a Makefile and how do you use it? Popular Linux commands Configuring ~/.bashrc Using grep, cut, sort and uniq Introducing GitHub Codespaces Compiling Python in Github CodeSpaces What is DevOps and how do you use it? Kaizen Methodology Learn Continuous Integration Learn key software engineering principles and best practices for building software. Learn both concepts and hands-on techniques for building software. Learn software craftsmanship. Additional Popular Resources Pytest Master Class AWS Solutions Architect Professional Course Github Actions and GitOps in One Hour Video Course Jenkins CI/CD and Github in One Hour Video Course AWS Certified Cloud Practitioner Video Course Advanced Testing with Pytest Video Course AWS Solutions Architect Certification In ONE HOUR Python for DevOps Master Class 2022: CI/CD, Github Actions, Containers, and Microservices MLOPs Foundations: Chapter 2 Walkthrough of Practical MLOps Learn Docker containers in One Hour Video Course Introduction to MLOps Walkthrough AZ-900 (Azure Fundamentals) Quick reference guide 52 Weeks of AWS Episode 8: Infrastructure as Code with CDK and AWS Lambda Learn GCP Cloud Functions in One Hour Video Course Python Devops in TWO HOURS! MLOps Platforms From Zero: DatMLOps Platforms From Zero: Databricks, MLFlow/MLRun/SKLearn AWS Machine Learning Certification In ONE HOUR Fast, documented Machine Learning APIs with FastAPI Zero to One: AWS Lambda with SAM and Python in One Hour AWS Storage Solutions 2022: EBS/S3/EFS/Glacier Python Bootcamp for Data Testing In Python book Minimal Python book Practical MLOps book Python for DevOps-Playlist.